Determinants of inflation expectations in Colombia (2004-2018) (2019)
This work uses an unrestricted VAR model with exogenous variables (VARX) to investigate the determinants of inflation expectations in Colombia for the period 2004 to 2018 based on information of survey-based inflation expectations. According to the literature review,specially the work of Ueda (2010), we identified and classified six for the model: i) endogenous: headline inflation, inflation expectations, output gap, nominal exchange rate, and policy interest rate and; ii) exogenous: oil price (Brent), climate shocks, and changes in the inflation targeting. According to empirical results, we identify an inertial effect in inflation expectations followed by a partial adaptive behavior based on headline inflation with significant responses in the very short run; on the other hand, the results when the inflation expectation measure is changed, indicates that to the extent that more sectors are considered in the survey, the larger the number of determinants of inflation expectations.